A novel case of reverse Takotsubo cardiomyopathy following brain biopsy. Issue 7 (28th June 2020) - Ives, Christopher W.; Smith, Phillip A.; Atchley, Travis J.; Pogwizd, Steven M.
Abstract: Reverse Takotsubo cardiomyopathy (rTTC) is a variant of Takotsubo cardiomyopathy (TTC) or stress‐induced cardiomyopathy. TTC is a transient cardiomyopathy resulting in a heart failure syndrome, triggered by emotional and/or physical stressors, that is usually self‐limited. rTTC is characterized by basal wall hypokinesis and apical wall hyperkinesis, the opposite of TTC. rTTC is more commonly associated with neurologic conditions, most notably intracranial hemorrhage. We present the first case in the literature of rTTC specifically following brain biopsy.